Strategi Penjualan Produk Jajanan Lokal Berbahan Ubi Oleh Siswa Ma. Arrahmah Jadddung Pragaan Sumenep Dalam Mempengaruhi Minat Beli Konsumen Menghadapi Persaingan Produk Impor - Lutfiyanto; Ach. Hisyam Rizky Setiawan AB (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2022)
Food ingredients are the main concern in making delicious and nutritious food. Food is usually produced from food after it has been processed or cooked. Food is usually produced from food after it has been processed or cooked. Meanwhile, traditional snack; include foods and drinks as well as mixed ingredients that have traditionally been used and developed in the area or community. In Indonesia, there are many kinds of traditional food ingredients. However, nowadays people's consumption patterns are changing a lot, the more modern food is getting, the lower of the level traditional food consumption among the people. This is due to the large number of modern processed food products, such as fast food. So that, some people prefer modern food over traditional food to make it more prestigious to serve. Modern food can be served quickly, besides that the appearance is also very tempting and the processing usually uses sophisticated tools, in contrast to traditional food which is too long in processing it. This is become a reason why many traditional food sellers change their sales products to modern food. However, there are still food sellers who continue to sell traditional food. However, the students of MA Ar-Rahmah made the foods by using local ingredients; such as sweet potato, taro, cassava, corn, and others are processed into modern food. Such as sweet potato steak, sweet potato roll cake, chocolate cassava chips, martabak corn rice, rice sempol, and jelly corn rice. However, to attract buyers, a sales strategy is a priority in developing these sales. So, the sales models must be designed according to the market nation.